Jornalismo hipermídia: desenhando a notícia científica na web - Velho, Ana Paula Machado (2007)
Under the optics of the concepts of Iuri Lótman, one of the exponents of the School of Tártu-Moscow s Semiotics of the Culture, the expressions of the culture are rebuilt from influences of socials, economics and politicals movements who mark the different historical moments of the humanity. These new information establishs itself in the semiosphere of the different groups, by intersection points, by sign borders, composing new cultural expressions. An example of this movement can be seen, today, in the products of mass media as the scientific journalism, this work corpus. These products are in a dialogic game with the forms of news organization of the digital environment: the cyberspace. Scientific news articles of periodicals and televisions are looking for new syntactic conformations, and one of them is the infoghrafic. The present research considers that this speech - the infoghrafic can be the border, the common expression between the analogical environment of the scientific journalism and the narrative of the digital environment, because both are support by a plurality of codes, in a hipertextual expression. The challenge of the work was to understand how this language can migrate to the space of a portable computer screen, composing a cyberspace coherent narrative. To point solutions was made an ample bibliographical survey about, in first place, the language and the design of the scientific journalism in periodicals environment, calling attention for its narrow relation with the infoghrafics. After that, was collected in many books what Communication researchers think about the adequacy of the journalism for the cyberspace. These data had supported an analysis of the forms of presentation, use and a categorization of the infoghrafics in the Web. All this material served of base to the description of the scientific infoghrafic migration to the WWW, and points a specific news format: the hipermedia journalism (JH). It can be defined as a potencialized expression of the infoghrafic, supported by the hipermedia language, which combines in connected archives the verbal, the imagistic and the sound. The result of the research can be seen, in the practical way, in the site Midiamania (www.midiamania.com.br)